The Predictive Value of Day one Serum Bilirubin Extent for Subsequent Increase Substantial Hyperbilirubinemia in Well Full Term Neonate in Mukalla Maternity and Child Hospital, Hadhramout,Yemen - Awad Bahwal , Saleh; Ahmed Jawass, Mazin; Salmeen Naji , Faiza (Diyala Journal of Medicine, 2021)
Background: Significant neonatal hyperbilirubinemia is a common cause of readmission following initial sending home from hospitals in healthy mature neonates. Objective: To determine the predictive ability of first 24th hr entire serum bilirubin (TSB) levels for later development of important hyperbilirubinemia in well mature neonates at Mukalla Maternity and Child Hospital (MMCH) in Mukalla city, Hadhramaut Governorate, Yemen. Patients and Methods: A cross sectional study of 150 well mature newborns was tracked with everyday serum total bilirubin detections for five days of life at Mukalla Maternity & Child Hospital between March 2019 and February 2020. Results: It was observed that 10%, 10%, 13.3% and 66.7%% of newborns were corresponding to high, high intermediate, low intermediate, and low risk zones respectively, while7.3% of newborns had developed significant hyperbilirubinemia and needed phototherapy. The day one bilirubin value of 5mg/dl had a sensitivity of 100% and specificity of 72%, the positive predictive value of 22%, and a negative predictive value of 100% in forecasting the risk of developing significant jaundice. Conclusion: A total serum bilirubin measurement may be applied as a useful screening test for each neonate at the first week of life, to foresee those at risk for later development of significant neonatal hyperbilirubinemia and permit for a harmless discharge from the hospital.